Improvement of qualitative and quantitative traits in soybean [Glycine Max (L.) Merrill] through gamma irradiation - Mehdi Arefrad; Ghorbanali Nematzadeh; Nadali Babaian Jelodar; Seyyed Kamal Kazemitabar (Journal of Plant Molecular Breeding, 2012)
Gamma irradiation was used at different doses (80, 160 and 240 Gy) on Glycine Max (L.) Merrill cv. Hill homogenous seeds. A single suitable M2 plant was selected and evaluated at M3 and M4 along with its parent and three other varieties as control in RCBD experiment in Sari Agricultural Sciences and Natural Resources University’s experimental field. M-80-709 and M-160-3429 mutant lines were significantly shorter (55.05 and 72.04 cm respectively). Their branch numbers were however significantly more (8.70 and 11.53 respectively) compared to the parent cultivar (80.82 cm and 6.10 respectively) and other genotypes (p≤0.05), when calculated on per plant basis. Besides, the M-160-3429 was characterized by highest grain yield and oil content (38.25 g and 19.22% respectively), in compare with its parent (12.73 g and 19.09% respectively) and all others control cultivars (p≤0.05). The M-160-3429 mutant line with high grain yield and oil content accompanied with some other favorite morphological traits can be considered as a new promising line of soybean for future studies. Results from this study suggested that mutation breeding procedures at the ranges of 80 to 160 Gy is a capable me‌thod for breeding higher grain yield including increasing the oil content as well.